Interesting and unusual clinical presentations in leprosy at a referral center - Pritam U Tayshetye; Vivek V Pai; Subhash A Khanolkar; Vikram Rathod; Ramaswamy Ganapati (Wolters Kluwer Medknow Publications, 2013)
Background: Leprosy is a disease of declining global endemicity but is still an important health-care problem in India. Pure neural leprosy is an important subset of presentations of leprosy in India. Leprosy is a known disease of the skin and nerves, but cases of pure neural involvement are relatively less. We hereby present 10 cases of pure neural leprosy in which the diagnosis of leprosy was difficult with routine methods. Materials and Methods: The study was conducted at the main referral center and satellite clinics of our organization. A retrospective analysis of patient records for the last four years was undertaken to identify patients presenting with predominantly neurological manifestations and uncommon presentations including those without skin lesions. The medical records of the patients were used as source of data. All the patients were subjected to a detailed clinical examination and bacteriological examination with slit-skin smears. Investigations like nerve biopsy, electromyography, and nerve conduction studies were done in patients with diagnostic difficulties. Results: Patients presented with neurological symptoms like paresthesias (60%), diminished sensations (40%), nonhealing ulcers (30%), and blisters (20%). All except one had thickened nerves on clinical examination. Slit-skin smear was negative in all but one patient. Nerve biopsy confirmed the diagnosis of leprosy in seven cases. Conclusion: Pure neural leprosy is difficult to diagnose with routine methods. The diagnosis should be considered, especially by neurologists and dermatologists, who are more likely to see such patients with predominant neural manifestations. The diagnosis should be confirmed with nerve biopsy to prevent delay in therapy and associated complications.